2015
DOI: 10.2174/1381612821666150130124354
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and Treating Depression in Older and Oldest Old

Abstract: Depression is very common in older people and it is associated with negative consequences such as functional decline, increased morbidity and mortality and higher healthcare costs. Despite this, it is still underdiagnosed and undertreated and the issue is particularly relevant for people older than 80 years. The main reasons for underdiagnosis are: atypical presentation, concomitant cognitive decline, inadequate diagnostic tools, and prejudice that depression is a normal part of ageing. On the other hand, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…In addition, recent research describes concomitant cognitive decline, inadequate diagnostic tools, and the prejudice that depression is a normal part of aging as the main reasons for underdiagnosis of depression in older adults. 41 However, it is remarkable that out of 163 elderly persons with depression, only 100 (61.4%) reported a recent diagnosis of depression. This underlines the fact that health care providers need an increased awareness of signs of depression in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent research describes concomitant cognitive decline, inadequate diagnostic tools, and the prejudice that depression is a normal part of aging as the main reasons for underdiagnosis of depression in older adults. 41 However, it is remarkable that out of 163 elderly persons with depression, only 100 (61.4%) reported a recent diagnosis of depression. This underlines the fact that health care providers need an increased awareness of signs of depression in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent research describes concomitant cognitive decline, inadequate diagnostic tools, and the prejudice that depression is a normal part of aging as the main reasons for underdiagnosis of depression in older adults 41. The risk for possible misdiagnosis is high particularly in those participants that consult physicians for somatic complaints of depression such as sleeping disorders 40 -symptoms frequent in elderly people.…”
mentioning
confidence: 99%
“…Looking specifically at attitudes towards psychotherapy and pharmacotherapy, a study among depressed primary care patients in the USA indicated a preference for counselling or psychotherapy over antidepressant medication (Gum et al 2006), which corresponds to population studies that consistently show stronger preferences for psychotherapy over pharmacotherapy (Schomerus et al 2012). However, only very few older persons with depression receive psychotherapy, most patients of older age receiving treatment are taking antidepressant medication (Morichi et al 2015). On the one hand, this is simply because guidelines for geriatric depression recommend antidepressant medication as an initial treatment (Alexopoulos, 2011), probably still reflecting the false belief that older persons do not benefit from psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Major depressive disorder (MDD) in the elderly has many negative consequences, including functional decline and a higher risk for other illnesses, such as dementia, and its healthcare costs are high (1, 2, 3). The current gold standard for the treatment of MDD is antidepressant medications (ADM) (4), but even with maximal treatment many patients fail to experience sustained remission of their depression (5).…”
Section: Introductionmentioning
confidence: 99%